Effects of Financial Market Imperfections on Indian Firms' Exporting Behavior - Hiro Ito; Akiko Terada-Hagiwara (Asian Development Bank (ADB), 2011)
Using data from more than 6,000 manufacturing firms in India for 1996–2008, we investigate the impact of financial constraints on the exporting behavior of Indian manufacturing firms while also focusing on the link between exchange rate movement and exports. We find that there is a strong degree of persistency in the exporting behavior of Indian manufacturing firms, reflecting the high fixed costs of entering foreign markets for Indian firms. A firm with a higher amount of net cash flows and smaller debt-to-asset ratios is more likely to become an exporter, indicating that a firm tends to self-finance its exporting without relying too much on external finances. Internal funds are especially important for firms that are not incumbent exporters to become exporters, and also for firms that do not enjoy technical advancement and high levels of productivity. When we divide the sample period into several subperiods, Indian firms have become less reliant on internal cash in recent years, but new exporters still rely on cash holdings to enter foreign markets. Over all, recent financial liberalization in India still does not allow the financial system to meet the stronger demand for funds by firms, especially small ones, though part of the stronger demand for funds are increasingly met by funds provided by foreign institutions. Based on our findings, improving the functionality of financial markets is an urgent issue to remove financial constraints that hinder Indian firms from entering export markets.
hdl:11540/2027
Keywords: F19; F36; G32; O16; 330; India; firm-level analysis; hysteresis hypothesis; financial constraint; market imperfection; Export; Liquiditätsbeschränkung; Währungsrisiko; Industrie; Indien